TRANSFORMASI DIGITAL PERPAJAKAN EDUKASI TOOLS PAJAK BERBASIS CORETAX DAN PROSPEK PROFESI AKUNTAN PAJAK BAGI SISWA SMK - Hijroh Rokhayati; Muhammad Adam Aptiansyah; Novita Febriany Kusumaningrum; Devika Devika (STAI Darul Qalam Tangerang, 2026)
The digital transformation of tax administration through the implementation of the Core Tax Administration System (Coretax) is a strategic step by the government to improve the efficiency, transparency, and quality of tax services, which simultaneously requires an increase in digital tax literacy among vocational education graduates. However, there remains a gap between students’ competencies and the needs of an industry that is increasingly technology-driven. This Community Service (PKM) activity aims to improve students’ understanding of digital taxation and provide insights into the career prospects of tax accountants in the era of digital transformation. The activity was conducted at SMK Negeri 1 Purwokerto, involving 33 students in the accounting program through interactive lectures, demonstrations of Coretax usage, discussions, and evaluations using pre-tests and post-tests. The material covered included the basic concepts of digital taxation, system-based tax administration workflows, as well as competencies and career opportunities in the field of tax accounting. The results of the activity indicate an improvement in students’ understanding, as reflected in the evaluation results, as well as increased active participation throughout the activity. In addition, students gained a clearer picture of career prospects as tax accountants. Thus, this activity demonstrates that practice-based education is effective in enhancing students’ digital tax literacy and work readiness; therefore, similar programs should be developed on an ongoing basis to support the strengthening of competencies in the digital age.